Interpreting contractual provision: extension of time - Ding, James Tse Wen (2015)
Construction projects that require extensions of time is a common phenomenon throughout the world. A significant number of such construction projects encounter some form of delays in the process and hence, the time for completion would be typically extended. Yet, the pertinent question is whether such the granting or disallowance of such extension of time is properly considered in light of the contractual background. The reality of this could be somewhat explained by the differing scope and complexity of the construction works undertaken in recent years. Increasing demands for more ambitious buildings or structures has inevitably led to construction designs that push the boundaries of the technical requirements involved. While the technicalities in the construction industry have been increasing in recent years, the development of law with regards to the application of extension of time has witnessed its own progression. The question therefore is whether the legal development moves in consonance with the practicality and commerciality required and expected from the construction professionals and to the industry itself. This paper will consider the approach taken in applying extension of time clauses and the factors involved. This would necessarily require an examination of the legal principles in contractual interpretation to provide the necessary depth to the overall analysis. Thereafter, the scope of extension of time within construction projects will be analysed from a legal perspective and the progression thereof is charted through the development of both statutes and case law. The term of reference would primarily draw from the Commonwealth jurisdictions given the dearth of approaches and case law that have emerged from this area.